1991
DOI: 10.1016/0006-2952(91)90048-a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of toluene and its metabolites on cerebral reactive oxygen species generation

Abstract: Abstract-The effects of toluene on lipid peroxidation and rates of reactive oxygen species (ROS) formation have been studied in isolated systems and in vivo. The induction of reactive oxygen species was assayed using the probe 2' ,7'-dichlorofluorescin diacetate (DCFH-DA). Toluene exposure (1 g/kg, 1 hr, i.p.) did not stimulate cortical lipid peroxidation as evaluated by measurement of conjugated dienes. Exposure to toluene, however, both in vivo and in vitro, caused a significant elevation of ROS formation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 27 publications
(25 reference statements)
2
33
0
2
Order By: Relevance
“…Prior studies with phenobarbital have also demonstrated that in vivo pretreatment accelerates hepatic metabolism of toluene and benzene, and thereby results in increased tolerance of the rats to the narcotic action of toluene (14). Pretreatment of rats IP 4611-H with metyrapone, a mixed-function oxidase inhibitor, significantly reduces the toluene-stimulated rate of ROS generation in cerebrocortical synaptosomal and hepatic microsomal fractions [7). This supports our finding that the first step in the catabolism of toluene (by cytochrome P450) can contribute to the enhancement of ROS formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies with phenobarbital have also demonstrated that in vivo pretreatment accelerates hepatic metabolism of toluene and benzene, and thereby results in increased tolerance of the rats to the narcotic action of toluene (14). Pretreatment of rats IP 4611-H with metyrapone, a mixed-function oxidase inhibitor, significantly reduces the toluene-stimulated rate of ROS generation in cerebrocortical synaptosomal and hepatic microsomal fractions [7). This supports our finding that the first step in the catabolism of toluene (by cytochrome P450) can contribute to the enhancement of ROS formation.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to toluene, in vivo and in vitro, was found previously to result in the induction of both ROS formation and lipid peroxidation in the liver, lung, kidney and various brain regions [7,8]. Toluene is metabolized through the oxidation of its methyl group by mixed-function oxidases to benzyl alcohol, followed by oxidation to benzaldehyde with alcohol dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable evidence for the induction of excess free radicals and ROS* generation by various neurotoxic aromatic solvents. These compounds include benzene [16], toluene [17][18][19], xylenes [19][20][21], and styrene [22]. There is less evidence for the induction of oxidative stress by aliphatic organic solvents.…”
mentioning
confidence: 99%
“…Exposure to toluene, both in vivo and in vitro, caused a significant elevation in ROS formation within cerebral cortical synaptosomal and microsomal fractions (Mattia et al, 1991). Reactive oxygen *species have been implicated in the action of a wide range of structurally and pharmacologically diverse compounds with an equally broad range of effects (Mason, 1982;Trush et al, 1982;Halliwell and Gutteridge, 1985).…”
Section: Introductionmentioning
confidence: 99%